The Effect of School Literacy Movement on Students’ Reading Interest and Reading Skills - Ariyanto, Bambang; Syaifudin, Rahmad; Misrodin, Misrodin; Hidayat, Tri Alim Saputra; Enriquez, Alexis Arizabal (CV. Creative Tugu Pena, 2022)
The article was to determine the effect of the school literacy movement on the reading skills of the students at State Elementary School 1BrajaYekti. This type of research was ex post facto. The sample of this research was 104 students. The sampling technique used random sampling. Analysis of the data used analysis prerequisite test consisting of normality test and linearity test, as well as the final analysis test consisting of simple regression test, simple correlation test, and coefficient of determination test. The results showed that: There was a positive and significant influence between the school literacy movement on reading interest as indicated by the value of tcount > ttable (6.315>1.980).There was a positive and significant effect between the school literacy movement on reading skills as indicated by the value of tcount > ttable (6.3397>1.980).The magnitude of the influence of the school literacy movement on reading interest was 25.6%.The magnitude of the influence of the school literacy movement on reading skills was 26.1%.' Based on the results of the research conducted, it was known that the school literacy movement could increase in reading literacy atState Elementary School 1BrajaYekti. Keywords: School Literacy, School Literacy Movement, Reading Skills